Efficacy of traditional Chinese exercise for obesity: A systematic review and meta-analysis - Yang, Ze; Huang, Kai; Yang, Yang; Xu, Qike; Guo, Qiaofeng; Wang, Xiang (Frontiers in Endocrinology, 2023)
Background: Obesity is considered one of the biggest public health problems, especially in the background of COVID-19 lockdown. It is urgent to find interventions to control and improve it. We performed this systematic review and meta-analysis to summarize the effect of Traditional Chinese Exercise on obesity. Methods: We searched PubMed, Embase, Cochrane Library, the China National Knowledge Infrastructure (CNKI), the Chinese Scientific Journal Database (VIP), the Chinese Biomedical Literature Database (CBM) and WanFang database for the updated articles published from the inception of each database to Jun, 2022. The randomized controlled trials of Traditional Chinese Exercise in weight reduction were included and related data were extracted. The random effects model was used to adjust for the heterogeneity of the included studies, and funnel plots were used to examine publication bias. Results: A total of 701 participants were included in the 10 studies. Compared with the control group, the outcome of body weight[MD =−6.10, 95%CI=(-8.79,-3.42)], body mass index[MD =−2.03, 95%CI=(-2.66,-1.41)], body fat mass[MD =−3.12, 95%CI=(-4.49,-1.75)], waist circumference[MD =−3.46, 95%CI= (-4.67, -2.24)], hip circumference[MD =−2.94, 95%CI= (-4.75, -1.30)] and waist to hip ratio[MD =−0.04, 95%CI=(-0.06,-0.03)] in intervention group had significant differences. Egger’s test and funnel plots showed that the potential publication bias of the included studies was slight (p=0.249). Conclusion: Traditional Chinese Exercise is an effective treatment for obesity, people with COVID-19 lockdown could do these exercises to control weight. However, a precise and comprehensive conclusion calls for RCTs on a larger scale with more rigorous designs considering the inferior methodological quality and limited retrieved articles.